China's Development Finance: What Issues for Reporting and Monitoring Systems?. (15th July 2014) - Xu, Jiajun; Carey, Richard
Abstract This article explores the implications of China's rise for global reporting and monitoring systems (RMSs) in the field of development cooperation. Beyond its fast‐growing – albeit still modest – foreign aid, China has emerged in the last decade as a globally pre‐eminent source of development finance. While China's endeavours are comparable to previous rising powers that strived to build linkages into global commodity chains and to participate in advanced industrial and technology value creation, what makes China distinct from OECD capital providers is its unprecedented scale, cohesive state‐market banking and enterprise institutions, and extensive utilisation of official finance for risk‐taking. This poses an existential crisis for DAC's ODA reporting system, helping to precipitate a wide‐ranging renovation process. Hence, China's intentions and capacities regarding the reporting and monitoring of its development finance have a potentially formative influence on the development of a new, wider DAC reporting system and on other international RMSs in the development finance field as well.